Introduction - Uusiautti, Satu; Yeasmin, Nafisa (Palgrave Macmillan, 2019)
Migration in the Arctic is an interesting but less studied phenomenon at the moment, one that influences various societal levels, such as education. This chapter introduces the contents of the book and discusses the multidimensional nature of migration in the Arctic.